Prioritizing Organizational Agility Strategies Using the Fuzzy Hierarchical Analysis Process - Sepideh Razaghi (Mathematical Statistician and Engineering Applications, 2023)
The enterprise accomplishment in implementation of resource planning system relies on choosing a system shows the highest rate of conformity with the organizational demands. Therefore, the enterprise resource planning (ERP) has greatly drawn attention. Since ERP is a costly and developed computer system, in past, the large enterprises only had utilized it. Though, recently, small and medium size enterprises have considered these systems, the present research is a practical attempt to provide an appropriate framework for selection of ERP in immigration companies. To measure the rate of significance of these standards, the descriptive –survey method was used. With regard to the existing literature, the effective criteria on selection of the system were determined and a questionnaire was applied to evaluate and prioritize the measures. The sample size includes 200 organizational professionals were randomly selected. Finally, through fuzzy analytical hierarchy process, a system was chosen that showed the highest degree of agreement with immigration companies needs and strategies